Design and Development of a Stock Data Collection System at PT. Indomarco Adi Prima Web Based - Tirta, Deazei; Purwanto, Dedi; Rizal, Chairul (Bahasa Indonesia, 2024)
This research aims to design and develop a web-based stock data collection system at PT. Indomarco Adi Prima in response to dynamic changes in the business environment and consumer trends. This system is designed to increase efficiency and accuracy in company stock management. The development methods used include requirements analysis, system architecture design, implementation and testing. The result is a web-based platform that allows management teams to access, manage and monitor inventory in real-time from various locations. The system also automatically integrates stock data with company operational processes, reducing the potential for human error and providing valuable analytical information. With the adoption of this system, PT. Indomarco Adi Prima can optimize stock management, respond quickly to market changes, and improve the quality of service to customers. This research makes a positive contribution in facing modern business challenges through the use of information technology to increase operational effectiveness.